The Determinants of E-Commerce Development in Indonesia: a Bibliometrical Analysis - Digdowiseiso , Kumba; Lantana , Dhieka Avrilia (CV ODIS, 2023)
The development of e-commerce is an economic disruption that occurs in the digital era. The e-commerce system provides benefits to society in being able to reach a wider market, providing efficiency and flexibility, and being able to provide transaction pattern information that can be accessed at any time. The Indonesian Central Statistics Agency noted that there has been an increase in the use of e-commerce in business activities in Indonesia (25.25% in 2020 and increased to 32.23% in 2021). Seeing these facts, ideally the development of e-commerce could be studied based on its determinants, but current research has not yet studied this comprehensively. Therefore, this research aims to (1) comprehensively cluster the determinants of e-commerce development in Indonesia using bibliometric studies, and (2) identify the density of determinants of e-commerce development in Indonesia comprehensively using bibliometric studies. The method used is quantitative-based bibliometrics. The research used publish or perish, and VOSviewer. The results show that there are four dominant keyword clusters that often appear, with the most dominant keyword being e-commerce, while based on density analysis, there are 28 topics that are often studied in studies of the determinants of e-commerce development in Indonesia.